2018
DOI: 10.3390/cli6010018
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Mitigation Strategies to Counteract Overheating in Urban Historical Areas in Rome

Abstract: Abstract:As urban overheating is increasing, there is a strong public interest towards mitigation strategies to enhance comfortable urban spaces, for their role in supporting urban metabolism and social life. The study presents an assessment of the existing thermal comfort and usage of San Silvestro Square in Rome during the summer, and performs the simulation of cooling strategies scenarios, to understand their mitigation potential for renovation projects. The first stage concerns a field analysis of the ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…In fact, Erell et al [24] underlined that use of cool colored materials may increase albedo substantially without altering visual appearance; however, because the human body is non-selective in its absorption of solar energy, the effect of albedo modification on thermal sensation could be negative. On the other hand, a combination of cool materials and trees showed positive effects both on outdoor temperatures and on thermal comfort as well, as demonstrated in a study by Shahidan et al [27] and Laureti et al [28]. Therefore, the use of cool coatings for the ground level (i.e., cool pavements) display different mitigation performances and require attention on the material characteristics of the surrounding area and on the morphology of the site.…”
Section: Overview On the Mitigation Potential Of Cooling Materials Anmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, Erell et al [24] underlined that use of cool colored materials may increase albedo substantially without altering visual appearance; however, because the human body is non-selective in its absorption of solar energy, the effect of albedo modification on thermal sensation could be negative. On the other hand, a combination of cool materials and trees showed positive effects both on outdoor temperatures and on thermal comfort as well, as demonstrated in a study by Shahidan et al [27] and Laureti et al [28]. Therefore, the use of cool coatings for the ground level (i.e., cool pavements) display different mitigation performances and require attention on the material characteristics of the surrounding area and on the morphology of the site.…”
Section: Overview On the Mitigation Potential Of Cooling Materials Anmentioning
confidence: 99%
“…For the present study, the cool materials investigated were selected from two studies carried out by Santamouris et al and Gobakis et al [18,64] and simulated recently in another urban open space of the historical tissue in the city of Rome [28]. Table 4 summarizes the materials database used in the initial scenario, S0; in the first renovation scenario S1 (green pavements + cool roof), and in the second renovation scenario S2 (cool pavements + green roofs), whereas Table 5 summarizes the albedo and leaf area density (LAD) coefficients of the tree species present in the University Campus and modelled in ENVI-met.…”
mentioning
confidence: 99%
“…As mentioned, Madrid has a Mediterranean climate that is characterized by hot summers. Studies in the Mediterranean climate have shown how urban green spaces can reduce the impact of urban heat [93,94]. A study carried out in Greece, Athens [95], found that the urban park on the western margin of Athens during the hot summer days could reduce daytime air temperature between 0.2 °C and 2.6 °C.…”
Section: Comparing the Cognitive Maps Significance At Different Distamentioning
confidence: 99%
“…As mentioned, Madrid has a Mediterranean climate that is characterized by hot summers. Studies in the Mediterranean climate have shown how urban green spaces can reduce the impact of urban heat [93,94]. A study carried out in Greece, Athens [95], found that the urban park on the western margin of Athens during the hot summer days could reduce daytime air temperature between 0.2 • C and 2.6 • C. In a similar study conducted in Lisbon, another Mediterranean city during the six days of summer 2007 and 2008 [96], the results showed that a 0.24 ha urban park was able to reduce the air temperature inside the park to 6.9 • C compared to its surrounding air temperatures.…”
Section: Comparing the Cognitive Maps Significance At Different Distamentioning
confidence: 99%
“…Geometric and surface characteristics regulate the partitioning of the surface energy balance (SEB) [2] and at any given location surface temperature-and near-surface air temperature under calm conditions [7,8]-is controlled by the surface's SEB [9]. impact on human outdoor thermal comfort is highly context-dependent [37,53,60] and few studies have been experimentally determined [52,54].…”
Section: Introductionmentioning
confidence: 99%